(untitled) (Stamford Journal of Microbiology, 2016)
Present review emphasized on the current state of cancer in Bangladesh and attempted to focus on the association of microorganisms in the development of cancer. People of Bangladesh have long been suffering from a range of diseases principally due to lack of required resources for disease diagnosis and subsequent treatment facilities. As a developing country with the lack of public awareness on hygiene, emerging infectious diseases conquered the countries. In this circumstance, the onset of cancer is appears as the incurable complications. In the country, cancer is an escalating fatal issue causing a mass scale of mortality each year. Moreover, while etiologic microorganisms are frequently detected during the common disease diagnosis, the pathogenic association with cancer formation remains obscure to the physicians in Bangladesh. While mortality and survival rate of cancer largely depends on the diagnosis and subsequent mitigation, hence it is essential to resolve the possible risk of cancer development in accordance to microbial attack. Stamford Journal of Microbiology, Vol.5(1) 2015: 30-35